2021
DOI: 10.1016/j.plrev.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The sense of should: A biologically-based framework for modeling social pressure

Abstract: We develop a model of social pressure, based on the metabolic costs of information. • We propose that conformity regulates the predictability of social environments. • We suggest that the experience of obligation stems from anticipated uncertainty. • We integrate disparate theories of mental inference with an embodied account. • We discuss the emergent consequences of others' expectations motivating behavior.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
141
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(145 citation statements)
references
References 262 publications
(411 reference statements)
4
141
0
Order By: Relevance
“… Frith and Frith, 2012 ; Timmermans et al , 2012 ). Additionally, making yourself predictable can help increase your chances of continuing to interact with others ( Coan and Sbarra, 2015 ), while potentially decreasing metabolic cost, which has been thought of as a function of prediction error ( Theriault et al , 2019 ). In brief, interpersonal similarity of friends can be considered as adaptive, as it might serve for uncertainty decrease in social interactions by fostering reliability ( Massen and Koski, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“… Frith and Frith, 2012 ; Timmermans et al , 2012 ). Additionally, making yourself predictable can help increase your chances of continuing to interact with others ( Coan and Sbarra, 2015 ), while potentially decreasing metabolic cost, which has been thought of as a function of prediction error ( Theriault et al , 2019 ). In brief, interpersonal similarity of friends can be considered as adaptive, as it might serve for uncertainty decrease in social interactions by fostering reliability ( Massen and Koski, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Global-scale environmental issues, from climate change to biosphere integrity [1], are creating an intense social pressure and a growing need for information with appropriate reliability and suitable spatial scale (from the local to global analysis and vice versa) that must be provided by the scientific community [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Social pressure is conformist behaviour with multiple determinations when an individual or group craves specific social attention; this leads them to behave in certain ways unconcerned of any prestige advantage [39]. A recent study conducted by [13] showed how computer-meditated communication is portrayed and influenced by robust rules of conduct, where communication arrangements are under constant social pressure.…”
Section: Social Pressure and Fear Of Missing Out As Stimulus To Relatmentioning
confidence: 99%